Distal Biceps Tendon Rupture Surgery: Changing Incidence in Finnish and Swedish Men Between 1997 and 2016 - Launonen, Antti P; Huttunen, Tuomas T; Lepola, Vesa; Niemi, Seppo T; Kannus, Pekka; Felländer-Tsai, Li; Berg, Hans E; Laitinen, Minna K; Mattila, Ville M (The Journal of hand surgery (American ed.), 2020)
Distal biceps tendon rupture is a relatively rare injury usually occurring with excess external extension force applied to a flexed elbow. The aim of this study was to examine the incidence of distal biceps tendon rupture surgery in the Finnish and Swedish adult population between the years 1997 and 2016. A secondary aim was to investigate the distal biceps rupture incidence in the Swedish population in 2001 to 2016. We assessed the number and rate of distal biceps tendon rupture surgery using the Finnish and Swedish Hospital Discharge Register as databases. The study included the entire Finnish and Swedish adult population aged 18 years and older between January 1, 1997 and of December 31, 2016. During the study period, 2,029 patients had a distal biceps tendon rupture in Finland, and the corresponding figure was 2,000 in Sweden. The rate of distal biceps tendon rupture surgery increased steeply, but equally, in both countries, in Finnish men from 1.3 per 100,000 person-years in 1997 to 9.6 in 2016, and in Swedish men from 0.2 in 1997 to 5.6 in 2016. The incidence of distal biceps tendon rupture in Sweden increased in men from 1.6 to 10.0 per 100,000 person-years from 2001 to 2016. There was a 7-fold and a 28-fold increase in the incidence of distal biceps tendon rupture surgery in Finnish and Swedish men during 1997 to 2016. The incidence of distal biceps tendon rupture rose 6-fold in Swedish men in 2001 to 2016. Prognostic IV.